2016
DOI: 10.1002/ana.24807
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin and factor X are elevated in multiple sclerosis patients

Abstract: Animal models have implicated an integral role for coagulation factors in neuroinflammatory diseases such as multiple sclerosis (MS) beyond their role in hemostasis. However, their relevance in humans requires further elucidation. This study aimed to determine whether levels of coagulation factors differ between patients with neuroimmunological disorders and respective controls. Individuals suffering from relapsing-remitting and secondary progressive MS had significantly higher prothrombin and factor X levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Coagulation activation promotes inflammation and conversely proinflammatory cytokines stimulate coagulation activation through multiple pathways. 6 , 7 Therefore, it is not surprising that levels of both coagulation factors including prothrombin and factor X (FX) 8 and procoagulant microparticles (MPs) are increased in MS compared with healthy individuals. 9 Moreover, proteomic analysis of post-mortem MS plaques identified coagulation factors in chronic active plaques which were not present in acute or active plaques.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulation activation promotes inflammation and conversely proinflammatory cytokines stimulate coagulation activation through multiple pathways. 6 , 7 Therefore, it is not surprising that levels of both coagulation factors including prothrombin and factor X (FX) 8 and procoagulant microparticles (MPs) are increased in MS compared with healthy individuals. 9 Moreover, proteomic analysis of post-mortem MS plaques identified coagulation factors in chronic active plaques which were not present in acute or active plaques.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known for a few years that the proinflammatory platelet activation factor (PAF) is increased a thousand-fold in the CSF of MS patients [55], resulting in the modulation of signals, including the production of nitric oxides, mitochondrial calcium influx and caspase activation. Surprisingly, recent studies demonstrated a concrete link between proteins of the coagulation system and the pathophysiology of MS [56][57][58]. Likewise, a recent study by Bellizzi et al showed that the PAF receptor in an animal model of MS mediates the over-excitation of hippocampal neurons and thus contributes to neuronal damage [59].…”
Section: Calcium-dependent Neurodegenerative Processes In Central Nermentioning
confidence: 99%
“…Multiple sclerosis (MS) is an autoimmune disorder of the central nervous system mediated by different molecular and cellular immune components, which lead to disseminated inflammatory lesions within the brain parenchyma and potential brain damage (Bhat and Steinman, 2009;Göbel et al, 2016a). The pathogenesis of MS has long been imparted to self-reactive T cells though B cells have also recently been found to play an important role in the development of MS (Disanto et al, 2012;Sospedra and Martin, 2005).…”
Section: Introductionmentioning
confidence: 99%